2017
DOI: 10.1371/journal.pone.0179413
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of rigid 3D image registration of high-resolution peripheral quantitative computed tomography images of healing distal radius fractures

Abstract: For accurate analysis of bone formation and resorption during fracture healing, correct registration of follow-up onto baseline image is required. A per-fragment approach could improve alignment compared to standard registration based on the whole fractured region. In this exploratory study, we tested the effect of fragment size and displacement on a per-fragment registration, and compared the results of this per-fragment registration to the results of the standard registration in two stable fractures and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Finite element analysis (FEA) with models derived from computed tomography (CT) scans is increasing in prevalence as a research and clinical diagnostic tool in orthopedics. [1][2][3][4][5][6][7][8] This technique is able to accurately capture both the complex geometries and localized material acquired by the CT scan to build representative animalspecific or patient-specific models. 9,10 FEA can then be used to simulate different loading scenarios and assess the structural biomechanics of the anatomy of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Finite element analysis (FEA) with models derived from computed tomography (CT) scans is increasing in prevalence as a research and clinical diagnostic tool in orthopedics. [1][2][3][4][5][6][7][8] This technique is able to accurately capture both the complex geometries and localized material acquired by the CT scan to build representative animalspecific or patient-specific models. 9,10 FEA can then be used to simulate different loading scenarios and assess the structural biomechanics of the anatomy of interest.…”
Section: Introductionmentioning
confidence: 99%
“…We also recommend that future work focuses on improving the precision of the μFE models by reducing repositioning error through image registration. We were unable to apply whole bone 3D image registration due to large differences in bone structure across follow-up scans; however, new image registration techniques have been developed to register individual bone fragments accounting for inter-fragmentary displacement ( de Jong et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Slight errors in registration and/or motion artifact may lead to inaccuracies in the global bone remodeling analysis. Previous studies using microCT in animal models have demonstrated that longitudinal analyses of bone remodeling produces better accuracy and precision when performed on a local region of interest rather than the whole bone [26][27][28]. It is likely that future studies using this bone remodeling analysis in the context of rheumatoid arthritis will be primarily concerned with bone changes around the region of an erosion, rather than the global changes throughout the bone.…”
Section: Discussionmentioning
confidence: 99%